Concept art del videojuego “Mad Side”, dirigido a desarrolladores y fanáticos de videojuegos - Pardo Sarango, Bryan Paúl (2019)
In this digital era, full of technology and in which the audiovisual media has gotten popularity. It is undeniable that videogames are an important part of the life of the major part of the whole world. Therefore, is so important to make a plan before we start with the creation of the visual content. Also, it is needed a big group of people to produce it. That is how this project is conceived. It will show the Concept Art of the “Mad Side” videogame, and has all the process of how a character, vehicle or prop is developed, from the sketch to the final piece rendered in Photoshop. The development of this project was by a descriptive investigation, it means that has made a search through different books, and in some digital articles. This was the theoretical livelihood. In addition, there was a recollection of visual references, that would help in the creation and the development of the different designs. To conclude, this book will help in the production of videogames. It has to make easy the developer is job. Additionally, it meant to be a good reference for people who wants to get in the videogame industry.